PARTICIPATORY BASED VILLAGE DEVELOPMENT: CASE STUDY IN HULAWA VILLAGE TELAGA SUB-DISTRICT GORONTALO DISTRICT - Hasanuddin, Nur Ain G.; Nani, Yacob Noho; Tohopi, Rustam (Public Policy Journal, 2024)
This study aims to find out how participatory village development is in Hulawa Village, Telaga District, Gorontalo Regency. The results of this study indicate that 1) To provide information, the Hulawa Village government is quite good at communicating with the community in providing information related to the planned development. 2) There is still a lack of community participation in terms of conducting consultations regarding village development, especially in terms of conveying what is their need. 3) In making joint decisions related to participatory development in Hulawa Village, Telaga District, Gorontalo Regency, it is good, that the community is active in participating in musrenbang for joint decision-making. 4) The joint action taken by the Hulawa Village government when there were obstacles faced by the Hulawa Village community was quite good. 5) In terms of providing this support, the Hulawa Village government has been good at providing support, especially in terms of increasing community participation related to village development. It can be concluded that community participation in development is still lacking, especially in conducting consultations related to participatory development. the community is active in participating in musrenbang for joint decision-making. The government of Hulawa Village has been good in providing support, especially in terms of increasing community participation related to village development.